Twisted river [large type] - MacDonald, Siobhan (Thorndike Press large print basic series., 2016)
In this gripping debut psychological thriller for fans of The Silent Wife and The Wicked Girls, two families in crisis arrange a holiday house swap. But what both wives see as the perfect chance to soothe a troubled marriage instead goes terribly wrong.